On the memory of R.W.B. Stephens - ŚLIWIŃSKI, A. S. (Archives of Acoustics, 1991)
On 28-th August 1090 passed away Raymond William Barrow Stephens, outstanding person in acoustical community and great friend of Poland and Polish acousticians.